Heterodyne opto-electro-mechanical micro-cavity accelerometer based on quantum confinement stark effect and preparation method of heterodyne opto-electro-mechanical micro-cavity accelerometer

By designing a heterodyne photoelectromechanical microcavity structure based on the quantum restricted Stark effect in the accelerometer, the shortcomings of traditional accelerometers in high-density photoelectric integration and sensitivity are solved, and high sensitivity, stability and a large range of acceleration detection are achieved.

CN119780472AActive Publication Date: 2025-04-08NANJING UNIV OF POSTS & TELECOMM
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411938717.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Traditional optical accelerometers have shortcomings in high-density photoelectric integration, sensitivity, stability and range, and the integration of light sources and sensors is complex, which may lead to mutual interference and excessive power consumption between devices.

Method used

A heterodyne photomechanical microcavity accelerometer based on the quantum restricted Stark effect was designed. Using the optical, electrical and mechanical characteristics of InGaN quantum well material, the optical microcavity region, stress-sensitive region and electroluminescent region of the beam overlap, and the light source and sensing components are combined into one to realize photomechanical integration.

Benefits of technology

It realizes acceleration detection with high sensitivity, high resolution, high stability and large ranges, avoids the limitations of traditional accelerometers, and has the advantages of miniaturization, low cost and anti-electromagnetic interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780472A_ABST
    Figure CN119780472A_ABST
Patent Text Reader

Abstract

The invention discloses a heterodyne opto-electro-mechanical microcavity accelerometer based on quantum confinement stark effect, which takes a silicon-based nitride epitaxial wafer as a carrier and comprises a silicon substrate layer, an aluminum nitride layer, a u-type gallium nitride layer, an n-type gallium nitride layer, a quantum well layer, a p-type gallium nitride layer and a SiO2 layer which are sequentially arranged from bottom to top, the p-type electrode is arranged on the p-type gallium nitride layer, and the n-type electrode is arranged on the edge of the n-type gallium nitride layer. According to a nitride material on a silicon substrate, two LDs are prepared in two areas of a beam by utilizing photoetching and ICP etching processes. Due to different stresses, the peak centers of the two LDs have a frequency difference. Under the power-on condition, the frequency difference of the acceleration load changes, and due to the change of the frequency difference, the magnitude of the acceleration can be sensed more stably and accurately.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of quantum electronics and optomechanical technology, and in particular relates to a heterodyne optomechanical microcavity accelerometer based on quantum confined Stark effect and a preparation method thereof. Background Art

[0002] Traditional optical accelerometers are mostly obtained by integrating silicon materials with external light sources, which makes it difficult to achieve high-density optoelectronic integration, and the sensitivity, stability and range of the devices need to be improved. In response to the above problems, this project intends to design dual lasers on the electrically pumped InGaN quantum well beam to construct an optomechanical integrated microcavity accelerometer. Under acceleration load, the piezoelectric polarization field caused by the mechanical strain of the beam induces the quantum confined Stark effect of the quantum well, causing the laser beat frequency of the electrically pumped beam laser to move, and the acceleration is sensed by the beat frequency change. This project will study the mechanism of laser mode movement of the beam laser under the above-mentioned multi-physical field mechanism, establish a quantitative relationship model between acceleration and spectral beat frequency movement, and explore the dynamic landscape of the InGaN quantum well band gap change under the piezoelectric polarization field and the coupled sensing mechanism of the mechanical strain of the beam optomechanical microcavity with the optical field and electric field. The following technical problems currently exist: 1. The design of a beam of the overall accelerometer must take into account the influence of the beam length on the luminescence, the realization of the quantum confined Stark effect, and the feasibility of realization in the actual processing process.

[0003] 2. When wiring the device, consider that the wiring position should not affect the normal operation of the device.

[0004] 3. Integrating the light source and sensor in the same microcavity structure is a complex task, especially when it comes to the optoelectronic and mechanical properties of the material, and it is necessary to consider that the performance of the light source and sensor may affect each other.

[0005] 4. Although optomechanical integration design has the potential to improve the integration of accelerometers, problems such as mutual interference between devices and excessive power consumption may arise during the miniaturization process. Summary of the invention

[0006] To solve the above problems, the present invention discloses a heterodyne optomechanical microcavity accelerometer based on quantum confined Stark effect, which utilizes the optical, electrical and mechanical properties of InGaN quantum well materials, so that the optical microcavity area, stress sensitive area and electroluminescent area of ​​the beam overlap, and the light source and the sensing component are combined into one, breaking the limitation of the separation of the light source and the sensing component of the traditional optical accelerometer, and is expected to achieve high sensitivity, high resolution, high stability and a large range of acceleration detection.

[0007] The invention relates to a quantum-confined Stark effect heterodyne optomechanical microcavity accelerometer, which uses a silicon-based nitride epitaxial wafer as a carrier and includes a silicon substrate layer, an aluminum nitride layer, a u-type gallium nitride layer, an n-type gallium nitride layer, a quantum well layer, a p-type gallium nitride layer, a SiO2 layer, a p-type electrode arranged on the p-type gallium nitride layer, and an n-type electrode arranged at the edge of the n-type gallium nitride layer. The silicon substrate layer is completely etched away, and only the square disk and the portion below the beam are retained to expose the shape of the beam and the square disk. The n-type electrode is arranged on the exposed n-type gallium nitride layer.

[0008] This accelerometer is a rectangular cavity connected by a beam in the middle. The two squares on both sides of the beam are hollowed out; the middle beam and a square electrode constitute a p-type electrode. At the same time, a layer of SiO2 is coated on the middle beam except for the two squares at half and about a quarter of the beam. The p-type electrode is deposited on the upper surface of the SiO2 layer on the middle beam; the n-type electrode is deposited on the n-type gallium nitride layer on the other side as a square electrode.

[0009] Furthermore, in the accelerometer of the present invention, the beam described above will deform under the action of static gravity, and the piezoelectric polarization field caused by the deformation will induce the quantum confinement Stark effect of the material of the InGaN quantum well, and due to the difference in stress, there will be a frequency difference between the peak centers of the two LDs. When powered on, the acceleration load frequency difference will change, and due to the change in the frequency difference, the magnitude of the acceleration can be sensed more stably and accurately.

[0010] The invention uses optical photolithography and ICP etching process and hydrofluoric acid and dilute nitric acid mixed solution wet etching process to prepare a beam. Reasonable process steps are designed, including the shape of the etching template, to obtain a single beam supported by a columnar shape and with smooth edges.

[0011] The method for preparing a heterodyne optomechanical microcavity accelerometer based on quantum confined Stark effect of the present invention comprises the following steps: Step 1: Spin-coat photoresist on the p-type GaN surface of the GaN-on-Si epitaxial wafer, and then use optical lithography to define a pattern of two square disks connected by a beam on the spin-coated photoresist layer; Step 2: Use electron beam evaporation technology to evaporate 300-500nm thick metal nickel on the surface of the defined pattern, then put the chip into acetone solution for ultrasonic treatment, then put the chip into ultrapure water for cleaning, and then put it into anhydrous ethanol and ultrapure water for cleaning, and finally remove the residual photoresist; a mask pattern of nickel is obtained.

[0012] Step 3: Etch down 2 μm-2.5 μm to the n-type gallium nitride layer using ICP etching technology, so as to transfer the pattern defined in the first step to the n-type gallium nitride layer of the silicon-based nitride wafer to obtain the structure of a beam of the accelerometer; Step 4: Use dilute nitric acid to remove metallic nickel, then immediately rinse in ultrapure water; Step 5: Evaporate a SiO2 layer on one beam of the accelerometer, but do not evaporate the SiO2 layer on two small squares in the middle of the beam and at one quarter of the beam.

[0013] Step 6: Spin-coat photoresist on a beam of the accelerometer and the outer square surface to ensure that the beam structure and the outer periphery will not be etched during the etching process, which plays a protective role; Step 7: Electron beam evaporation technology is used to evaporate 300-500nm thick metal nickel on the surface of the defined pattern, and then the epitaxial wafer is placed in an acetone solution for ultrasonic cleaning, and then placed in anhydrous ethanol and ultrapure water for cleaning in turn, and finally the residual photoresist is removed to obtain a mask pattern of nickel; Step 8: Use ICP etching technology to etch the pattern downward until the middle is hollowed out; Step 9: Using electron beam evaporation technology to evaporate a positive electrode on the upper surface of the p-type region electrode pattern, and to evaporate a negative electrode on the upper surface of the n-type region electrode pattern, so that the p-type gallium nitride layer and the n-type gallium nitride layer are respectively plated with positive and negative electrodes, and finally the residual photoresist is removed to obtain the p-type region electrode and the n-type region electrode; Step 10: Use a mixture of hydrofluoric acid and dilute nitric acid to wet-etch silicon until the bottom of the silicon substrate layer, so that silicon columns and a bottom surface supporting this structure are formed in the silicon substrate layer to form a suspended beam structure.

[0014] Furthermore, in the method of the present invention, both the positive electrode and the negative electrode are vapor-deposited Au / Ni.

[0015] Beneficial effects: Compared with the prior art, the present invention has the following advantages: 1. The present invention uses a single epitaxial wafer, does not need to grow different materials, has a simple structure, small size, and is easy to integrate. Compared with the current optical accelerometers made of passive materials such as SI and SIN, it has the advantages of miniaturization, low cost, high sensitivity, anti-electromagnetic interference, and impact resistance. 2. This project intends to design dual lasers on the electrically pumped InGaN quantum well beam to construct an optomechanical integrated microcavity accelerometer. Under acceleration load, the piezoelectric polarization field caused by the mechanical strain of the beam induces the quantum confined Stark effect of the quantum well, causing the laser beat frequency of the electrically pumped beam laser to move, and the magnitude of the acceleration is sensed by the change in the beat frequency. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Side view of the InGaN quantum well optomechanical microcavity accelerometer based on the quantum confined Stark effect Figure 2 Top view of the InGaN quantum well optomechanical microcavity accelerometer based on the quantum confined Stark effect.

[0017] Figure 3 Process flow chart of InGaN quantum well optomechanical microcavity accelerometer based on quantum confined Stark effect.

[0018] Figure 4 Stress distribution on the accelerometer surface under the net gravity field.

[0019] Figure 5 Displacement deformation of the middle beam of the accelerometer under the net gravity field.

[0020] In the figure, there are: 1-silicon substrate layer, 2-aluminum nitride layer, 3-u-type gallium nitride, 4-n-type gallium nitride layer, 5-quantum well layer, 6-p-type gallium nitride layer, 7-SiO2 layer, 8-p-type electrode, 9-n-type electrode, 10-stress sensitive area; 11-beam. DETAILED DESCRIPTION

[0021] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. It should be noted that the words "front", "rear", "left", "right", "upper" and "lower" used in the following description refer to directions in the accompanying drawings, and the words "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively. Example

[0022] like Figure 1-2 As shown, the present invention uses a silicon-based nitride epitaxial wafer as a carrier, and from bottom to top, there are a silicon substrate layer 1, an aluminum nitride layer 2, a u-type gallium nitride layer 3, an n-type gallium nitride layer 4, a quantum hydrazine layer 5, a p-type gallium nitride layer 6, a SiO2 layer 7, and a p-type electrode 8 arranged on the p-type gallium nitride layer 6 and a square n-type electrode 9 arranged on the edge of the n-type gallium nitride layer 4. The silicon substrate layer is completely etched away, leaving only the middle beam and the lower part around the accelerometer, and the n-type electrode is arranged on the side of the exposed n-type gallium nitride layer. The accelerometer is provided with a beam with a mass block located between two square disks. The beam width is 20μm. The accelerometer covers the p-type electrode of the p-type gallium nitride layer, and the p-type electrode consists of a beam and a square electrode, the beam length is 300μm, the square electrode is 30μm long and 20μm wide, and the electrode thickness is 120nm.

[0023] like Figure 3 As shown, the method for preparing a heterodyne optomechanical microcavity accelerometer based on the quantum confined Stark effect of this embodiment takes the preparation of a square disk with a side length of 30 μm, a width of 20 μm, and a beam length of 300 μm as an example, and the preparation process is as follows: Step 1: Clean the purchased commercial silicon substrate GaN epitaxial wafer with acetone, anhydrous ethanol and ultrapure water in sequence by ultrasonic cleaning (5 minutes), and then blow dry with nitrogen; use a coating machine to spin-coat the front side of the epitaxial wafer (the upper surface of the p-type nitride layer 5) with photoresist AZ-5214 at a speed of 4000 rpm for 40 seconds (the thickness of the photoresist is 1.5 microns).

[0024] Optical lithography technology is used, and then optical lithography technology is used to define two square patterns connected to a beam with a mass block on the spin-coated photoresist layer. The lithography machine model is MA6.

[0025] Step 2: Use electron beam evaporation technology to evaporate 350nm of metal nickel on the surface of the P-type gallium nitride layer 6, and then remove the residual photoresist.

[0026] Step 3: Etch the nitride layer downwards to the n-type gallium nitride layer 4 using ICP etching technology, so as to transfer the pattern defined in the first step to the n-type gallium nitride layer 3 of the silicon-based nitride epitaxial wafer, and obtain a beam structure of the accelerometer; The epitaxial wafer is then placed in a dilute nitric acid solution to remove the residual metallic nickel, and then placed in anhydrous ethanol and ultrapure water to clean it; Step 4: Evaporate a SiO2 layer on a beam in the middle of the accelerometer, but do not evaporate a SiO2 layer on a small square at the tail of the beam.

[0027] Step 5: Use a coating machine to spin-coat the front side of the epitaxial wafer (the surface of a beam structure and the surrounding square surfaces) with a speed of 4000 rpm and a spin coating time of 40 seconds (the thickness of the photoresist is 1.5 μm).

[0028] Step 6: Use electron beam evaporation technology to evaporate 420nm of metal nickel on the surface of the n-type gallium nitride layer 4, and then remove the residual photoresist.

[0029] Step 7: Use ICP etching technology to etch the pattern downward until the middle is hollowed out; The epitaxial wafer is then placed in a dilute nitric acid solution to remove the residual metallic nickel, and then placed in anhydrous ethanol and ultrapure water to clean it; Step 8: Use a mixture of hydrofluoric acid and dilute nitric acid to wet-etch silicon until the bottom of the silicon substrate layer, so that a silicon column and bottom surface supporting this structure are formed in the silicon substrate layer, so that a beam structure of LD is suspended. The etching gas is a mixture of HF and HNO3, the etching time is 1 minute, and finally remove the residual photoresist.

[0030] COMSOL Multiphysics is a multi-physics simulation platform involving multiple modules such as fluid, electromagnetic, heat transfer, structure, chemical engineering, acoustics, equations, etc. It only needs to give the coupling relationship with the physical field in various scenarios to express it using the software. This invention was simulated using this software.

[0031] The device is studied in a steady state under a net gravity field, and the stress distribution on the device surface is shown in Figures 4 and 5. The device is studied in a steady state under a net gravity field, and the stress distribution on the device surface is shown in the following figure. It can be found that the stress at one quarter of the beam and the stress in the middle of the beam are significantly greater than the stress around it.

Claims

1. A heterodyne optomechanical microcavity accelerometer based on quantum confined Stark effect, characterized in that: The accelerometer uses a silicon-based nitride epitaxial wafer as a carrier, and comprises a silicon substrate layer (1), an aluminum nitride layer (2), a u-type gallium nitride layer (3), an n-type gallium nitride layer (4), a quantum well layer (5), a p-type gallium nitride layer (6), and a SiO2 layer (7) arranged in sequence from bottom to top, a p-type electrode (8) arranged on the p-type gallium nitride layer (6), and an n-type electrode (9) arranged at the edge of the n-type gallium nitride layer (4). The four sides of the silicon substrate layer (1) are completely etched away, leaving a middle beam (11) and the portion below the beam (11); after power is turned on, two stress sensitive areas (10) of the beam (11) emit laser LD.

2. The quantum confined Stark effect heterodyne optomechanical microcavity accelerometer according to claim 1, characterized in that: The accelerometer is a rectangular cavity connected in the middle by a beam (11). Two squares on both sides of the beam (11) are hollowed out. The middle beam and a square electrode form a p-type electrode (8). At the same time, a layer of SiO2 layer (7) is plated on the middle beam except for two squares at one-half and about one-quarter of the beam. The p-type electrode (8) is deposited on the upper surface of the SiO2 layer (7) on the middle beam. The n-type electrode (9) is deposited on the n-type gallium nitride layer (4) on the other side as a square electrode.

3. The quantum confined Stark effect heterodyne optomechanical microcavity accelerometer according to claim 3, characterized in that: Since the stresses in the two stress sensitive areas (10) of the beam are different, there will be a frequency difference between the peak centers of the two LDs; when power is turned on, the frequency difference of the acceleration load will change.

4. A method for preparing a heterodyne optomechanical microcavity accelerometer based on quantum confined Stark effect, characterized in that: The method comprises the following steps: The first step is to spin-coat a photoresist on the upper surface of the p-type gallium nitride (6) of the silicon-based gallium nitride epitaxial wafer, and then use optical lithography technology to define a pattern of two square disks connected by a beam on the spin-coated photoresist layer; Step 2: Electron beam evaporation technology is used to evaporate 300-500nm thick metal nickel on the upper surface of the defined pattern, and then the wafer is placed in an acetone solution for ultrasonic treatment, and then the wafer is placed in ultrapure water for cleaning, and then placed in anhydrous ethanol and ultrapure water for cleaning in turn, and finally the residual photoresist is removed; a mask pattern of nickel is obtained; Step 3: Etching 2 μm-2.5 μm down to the n-type gallium nitride layer (4) using ICP etching technology, thereby transferring the pattern defined in the first step to the n-type gallium nitride layer (4) of the silicon-based nitride wafer, and obtaining a beam structure of the accelerometer; Step 4: Use dilute nitric acid to remove metallic nickel, then immediately rinse in ultrapure water; Step 5: Evaporate the SiO2 layer on the middle beam of the accelerometer, but do not evaporate the SiO2 layer on the two small squares in the middle of the beam and at one quarter of the beam; Step 6: Spin-coat photoresist on a beam of the accelerometer and the outer square surface to ensure that the beam structure and the outer periphery will not be etched during the etching process, which plays a protective role; Step 7: Electron beam evaporation technology is used to evaporate 300-500nm thick metal nickel on the surface of the defined pattern, and then the epitaxial wafer is placed in an acetone solution for ultrasonic cleaning, and then placed in anhydrous ethanol and ultrapure water for cleaning in turn, and finally the residual photoresist is removed to obtain a mask pattern of nickel; Step 8: Use ICP etching technology to etch the pattern downward until the middle is hollowed out, and finally clean the remaining photoresist; Step 9: using electron beam evaporation technology to evaporate a positive electrode on the upper surface of the p-type region electrode pattern and to evaporate a negative electrode on the upper surface of the n-type region electrode pattern, so that the p-type gallium nitride layer (6) and the n-type gallium nitride layer (4) are respectively coated with positive and negative electrodes, and finally removing the residual photoresist to obtain a p-type region electrode (8) and an n-type region electrode (9); Step 10: Wet-etch silicon using a mixture of hydrofluoric acid and dilute nitric acid until the bottom of the silicon substrate layer (1), so that silicon columns and a bottom surface supporting the structure are formed in the silicon substrate layer (1), forming a suspended beam structure.

5. The method for preparing a heterodyne optomechanical microcavity accelerometer based on quantum confined Stark effect according to claim 4, characterized in that: The positive electrode and the negative electrode are both evaporated Au / Ni.

Citation Information

Patent Citations

  • Si based HEMT embedded micro accelerator and production method thereof

    CN102401840A

  • Embedded highly-sensitive micro-accelerometer based on e index semiconductor device

    CN102507978A

  • Miniature combined uniaxial cold atom inertial sensor and measuring method thereof

    CN105674972A

  • Electric pump acceleration sensor and preparation method thereof

    CN113624992A

  • On-chip InGaN quantum hydrazine beam triaxial accelerometer based on electric pump and preparation method thereof

    CN116477562A